(untitled) (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to discuss and describe the inheritance of the Ngadu Tanduk Dance in Siulak Panjang Village, Siulak District, Kerinci Regency. The research uses a qualitative descriptive method. The research instrument is the researchers themselves, assisted by supporting instruments such as a mobile phone camera and writing tools. The data in this research consists of primary and secondary data. Data collection techniques are conducted through literature study, observation, interviews, and documentation. The steps of data analysis are data collection, data reduction, data presentation, and drawing conclusions. The results show that the inheritance of the Ngadu Tanduk Dance in Siulak Panjang Village uses a closed inheritance system. The dance is passed down from generation to generation for young people who have an interest and dedication in learning it. The process of passing it down is done through practice, direct observation, and involvement in traditional performances or cultural activities. The Ngadu Tanduk dance is taught directly through practice sessions between the teacher and the prospective dancer, where the teacher demonstrates the movements and the participant repeatedly follows and practices them. The movements in the Ngadu Tanduk dance include: 1) greeting movements, 2) buffalo searching for an opponent, 3) horn-clashing movements. However, there are some challenges in passing down the Ngadu Tanduk dance, such as declining interest among the younger generation in the Depati Mangku Bumi lineage towards traditional arts, the rise of modern entertainment, and limited performance opportunities. Even so, the people of Siulak Panjang Village still try to keep the Ngadu Tanduk Dance alive through practice sessions and performances at traditional events, cultural festivals, wedding receptions, and welcoming guests. Therefore, the Ngadu Tanduk Dance remains one of the local cultural heritages that continues to be preserved and passed down from generation to generation.